ENTROPY METHOD FOR EARTHQUAKE VOLATILITY - Metin Karakas, Ayse; Calik, Sinan (Yildiz Technical Univ, 2020)
In this study, we obtained the volatility of 1. and 2. degree earthquake zones on the same fault line by using entropy method. The application of entropy in earthquake can be regarded as the extension of information entropy and probability theory. The entropy theory applied to derive the most likely univariate distributions subject to specified restriction by applying the principle of maximum entropy. These findings indicate the necessity of more detailed studies for a more comprehensive understanding the nature of Earthquake.
Keywords: Renyi entropy; the shannon entropy; tsallis entropy; Approximate Entropy (ApEn)